The Effect of Sport Participation and Age on Peak Handgrip Strength - Karatrantou Κωνσταντίνα; Gerodimos Βασίλης; Angelakou Μαγδαληνή; Psychou Δήμητρα; Papadimitriou Δήμητρα; Tsiakaras Νίκος (Inquiries in Physical Education and Sport, 2012)
Handgrip strength (HG) is an important element to succeed in several sports such as wrestling, team sports, tennis, climbing etc. Therefore, this study examined the effect of sport participation and age on peak handgrip strength. Two hundred and seventy participants: 90 Greco-Roman wrestlers, 90 basketball players and 90 untrained males were participated in the study. Participants were assigned according to their chronological age into thee agegroups: children (10.6 ± 0.7 years), adolescents (14.1 ± 0.7 years) and adults (24.2 ± 4.6 years). A portable hydraulic dynamometer (Jamar) was used for the HG measurement. The absolute HG (kg) of the preferred hand was evaluated, and the relative HG per unit of body mass (kg/kg) was calculated. A two-way analysis of variance (sport x age, 3 x 3) and Tukey’s posthoc analysis were used to analyze the data. The results revealed statistically significant «sport» x «age» interaction for maximal handgrip strength (absolute and relative terms). Handgrip strength (absolute and relative terms) was similar in children and adolescents wrestlers, basketball players and controls, whereas, differences were observed among wrestlers, basketball players and controls in adults. Adult wrestlers (p<.001) and basketball players (p <0.05) exhibited significantly greater peak HG than their control peers. Also adults wrestlers demonstrated significantly greater peak HG (p <0.05) than their basketball players adults (p<.001). Additionally, the results showed a significant age-related increase in peak HG (absolute and relative terms) irrespective of sport, with the exception of untrained adolescents vs. adults where no differences in relative HG were observed.